Unidimensional longitudinal strain: a simple approach for the assessment of longitudinal myocardial deformation by echocardiography - Aurich, Matthias; Fuchs, Patrick; Müller-Hennessen, Matthias; Uhlmann, Lorenz; Niemers, Matthias; Greiner, Sebastian; Täger, Tobias; Hirschberg, Kristóf; Ehlermann, Philipp; Meder, Benjamin; Frankenstein, Lutz; Giannitsis, Evangelos; et al. (Journal of the American Society of Echocardiography, 2018)
Background - Impaired left ventricular (LV) longitudinal function (LF) is a known predictor of cardiac events in patients with heart failure, but two-dimensional strain imaging, the reference method to measure myocardial deformation, is not always feasible or available. Therefore, reliable and reproducible alternatives are needed. The aim of the present study was to evaluate unidimensional longitudinal strain (ULS) as a simple echocardiographic parameter for the assessment of LV LF. - Methods - Two hundred two patients with dilated cardiomyopathy who had their first presentation in the authors' cardiology department, as well as the same number of age- and gender-matched control subjects, were prospectively included in this study. ULS was compared with global longitudinal strain (GLS), the current gold standard for LV LF assessment by echocardiography. Uni- and multivariate Cox regression analyses were conducted to evaluate the prognostic value of ULS. - Results - LV LF was higher in the control group compared with patients: GLS −19.5 ± 1.7% versus −12.6 ± 4.8% and ULS −16.3 ± 1.5% versus −10.2 ± 3.9% (P < .001 for each). Correlation between ULS and GLS was excellent (r = 0.94), while Bland-Altman plots revealed lower values for ULS (bias −2.76%, limits of agreement ±3.31%). During a mean follow-up time of 39 months, the combined end point of cardiovascular death or hospitalization for acute cardiac decompensation was reached by 28 patients (13.9%). GLS (hazard ratio, 1.21; 95% CI, 1.10-1.34; P < .001) and ULS (hazard ratio, 1.24; 95% CI, 1.12-1.39; P < .001) had comparable prognostic impact on patient outcomes. - Conclusions - ULS might be an alternative echocardiographic method for the assessment of LV LF, with similar diagnostic and prognostic value compared with GLS.